Alternative energy pathways in Southern Ocean food webs: Insights from a balanced model of Prydz Bay, Antarctica. (April 2020) - McCormack, Stacey A.; Melbourne-Thomas, Jessica; Trebilco, Rowan; Blanchard, Julia L.; Constable, Andrew
Abstract: In recent years, there has been a shift away from the long-standing paradigm in which a short, krill-dominated food chain was considered to be the central element in Southern Ocean food webs. Instead, there is now increasing recognition that alternative energy pathways through mid-trophic level groups (mesopelagic fish and squid) may be equally (if not more) important than the krill pathway in many regions. Ecosystem models are a valuable tool to synthesise existing data on the structure of marine food webs and to visualise and quantify alternative energy pathways. In this study we develop a static mass balance food web model for the southern Kerguelen Axis region (Prydz Bay and Princess Elizabeth Trough) to evaluate the importance of alternative energy pathways through mid-trophic level groups, including fish, squid and krill, in maintaining energy flow to top predators within East Antarctica. Our model reveals several major trophic pathways distinct from, and equally important to the Antarctic krill ( Euphausia superba ) pathway. Using simple scenarios of reductions in krill biomass, we investigate how the system might switch to a state dominated by fish and squid pathways with the response of krill-reliant predators strongly dependent on their ability to switch to other prey sources. We conclude by discussing what these findings might suggest for the future vulnerability of East Antarctic food webs and the implications for future modelling work in the region.